Premature oral aging: A literature review (Research, Society and Development, 2024)
Premature oral aging (PEA) is a condition that has become frequent among young people, characterized by clinical manifestations that indicate accelerated wear of oral tissues, resulting in an aged appearance of the oral cavity. The main aim of this study was to investigate the causes and possible associations of EPB with environmental factors and behavioral habits. The research used an analysis based on a bibliographic survey of premature oral aging and its etiological factors. Patients generally only identify EPB when they experience discomfort such as dentinal hypersensitivity or when aesthetics are compromised, leading to a late diagnosis. This study shows that the causes and factors that affect the clinical characteristics of Premature Oral Ageing (PEA) require not only dentistry, but also other areas to be involved in its proper treatment. It is therefore necessary for dentists to adopt a multidisciplinary approach, combined with special attention to prevention.